Exploring the Potential of Blockchain Technology for Zakat Administration in Indonesia - Chita Ayu Putri (Center of Strategic Studies (PUSKAS) BAZNAS, 2022)
Zakat is believed to be able to alleviate or at least reduce poverty in Muslim-majority countries. Indonesia, the largest Muslim-majority in the world, is claimed to have a huge potential for zakat. Unfortunately, the zakat collection rate based on the total zakat potential in the country is low. This study will investigate the potential for Blockchain technology in enhancing zakat collection in Indonesia. Through a survey, the study assesses the perception of a sample of 312 individuals in Jakarta regarding the levels of credibility of the existing fintech application offered through BAZNAS and assesses the need for blockchain adoption. Officials from the BAZNAS is also interviewed to determine perception and readiness of blockchain adoption for zakat collection. Lastly, this research shows that individuals in Jakarta demand credibility in paying zakat, and their acceptance to a new technology is high. While BAZNAS as zakat institution that has adopted blockchain in initial stage admit the usefulness of blockchain.